The Bangladesh economy in transition - Quibria, M. G. (Muhammad Ghulam); Asian Development Bank. (Delhi ; New York : Oxford University Press, 1997)
Revised version of papers presented in a conference held in Bangladesh, 1993, organized by the Asian Development Bank in collaboration with the Academy for Planning and Development, Bangladesh.
"Published for the Asian Development Bank."
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Economic policy -- Congresses